Prematurity: parental stress, temperament and infant development (European Journal of Child Development, Education and Psychopathology, 2013)
The study was aimed at exploring the association between parenting distress, maternal perception of infant temperament and level of infant development when a preterm birth occurs. At 3 months of corrected age, 78 preterm infants and their mothers were compared with 73 term infants, using: Parenting Stress Index-Short Form (PSI-SF); Italian Questionnaires of Temperament (QUIT; 1-12 months); Griffiths Mental Development Scales (GMDS; 0-2 years). Results showed that preterm infants’ mothers showed higher level of distress and perceived their infants as more difficult. Moreover, in GMDS preterm infants reported lower scores in Hearing-Language, Performance and General Quotients compared to full term ones. Significant predictors of higher maternal distress were preterm birth, lower infant Locomotor and Personal-Social development and perception of lower Positive Emotionality, higher Negative Emotionality. Preterm birth has a deeply stressful impact that can be exacerbated by the perception of the disparity between the demands of neonatal care and resources available.